(untitled) (CIPEEX, 2025)
INTRODUCTION: Cyclophosphamide (CYC) is an agent used to treat neoplasms and autoimmune diseases. This study evaluates the efficacy of CYC in the treatment of systemic lupus erythematosus (SLE), analyzing possible adverse effects, including neoplastic events. METHODOLOGY: Systematic searches were conducted in the BVS, PubMed, SciELO, and LILACS databases using specific descriptors on the efficacy of cyclophosphamide in the treatment of SLE. Articles in English and Portuguese published between 2000 and 2023 were included, excluding theses, unpublished dissertations, duplicate articles, and articles published before 2000. RESULTS AND DISCUSSION: The search resulted in 143 studies, of which 14 were selected for analysis. Cyclophosphamide is widely used in the treatment of systemic lupus erythematosus (SLE), especially in severe cases such as lupus nephritis (LN). Studies demonstrate its efficacy in reducing disease activity and inducing remission. However, prolonged use can lead to significant adverse effects, including hematologic toxicity and neoplastic risks. High doses are associated with serious adverse events and an increased risk of cervical neoplasia. Strategies such as low-dose cyclophosphamide administration and combination with other immunosuppressants have shown similar efficacy with fewer side effects. CONCLUSION: CYC is effective in reducing SLE activity and decreasing the need for corticosteroids, with lower dose regimens presenting fewer adverse effects. Combination with rituximab may improve clinical outcomes in refractory cases, but prolonged toxicity requires close monitoring and dose adjustments.